Predicting Stress Intensity Factor (KI) of Single Edge Crack Using Displacement Extrapolation Method - Firmansyah, Hendrix Noviyanto (Institut Teknologi Dirgantara Adisutjipto, 2018)
Cracks that occur in the structure will be very dangerous if left alone. Cracks can propagate and will eventually cause the structure to fail. Cracks that occur will cause singularity at the end of the crack, and the stress level is very high or reaches without limit (infinity). Stress intensity factor (SIF) is used to determine behavior of structures with crack. One of method that can predict SIF is displacement extrapolation method. Displacement extrapolation methods predict SIF by nodal displacement near end of crack. This research is to predict SIF of a thin plate with a single edge crack of 1.27 mm. The crack mode used in this research is mode I (opening mode) with a tension stress of 60 MPa. Nodal displacement for calculating SIF is taken from result of analyzing the cracked model using Patran / nastran. SIF prediction result from displacement extrapolation then to be compared with the results of analytical calculation.